Verdigting: ’n Beplanningstrategie vir die toekoms? - Verreynne, Saar; Steyn, Das (Acta Structilia, 1997)
South Africa currently undergoes certain processes of social and political change. These processes force planning itself to change. Urbanisation increases the demand for land for urban expansion. The purpose of this article is to examine diffirent densification methods which can be implemented in urban areas. The continual need for land for urban expansion could therefore be limited. This article also· seeks to analise the advantages of densification. *This article is written in Afrikaans.